2006
DOI: 10.1073/pnas.0509989103
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex maps articulatory features of speech sounds

Abstract: The processing of spoken language has been attributed to areas in the superior temporal lobe, where speech stimuli elicit the greatest activation. However, neurobiological and psycholinguistic models have long postulated that knowledge about the articulatory features of individual phonemes has an important role in their perception and in speech comprehension. To probe the possible involvement of specific motor circuits in the speech-perception process, we used event-related functional MRI and presented experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
461
5
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(532 citation statements)
references
References 62 publications
(78 reference statements)
47
461
5
4
Order By: Relevance
“…Thus, the superior temporal cortex has been shown to be involved in the perception and production of language (Buchsbaum et al, 2001) and object naming (Hirsch, Moreno, & Kim, 2001). Similarly, the area in left inferior precentral gyrus (BA 6), extending into the inferior frontal gyrus (BA 9) has been proposed to be involved in ariculatory processes (Pulvermüller, et al, 2006) and sub-vocalization activity (Dietz, et al, 2005), as well as in certain naming and word-retrieval tasks (Etard, et al, 2000;Grabowski, et al, 1998). Therefore, like the left insula, these regions may be involved in lexical retrieval or covert naming of the F and U objects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the superior temporal cortex has been shown to be involved in the perception and production of language (Buchsbaum et al, 2001) and object naming (Hirsch, Moreno, & Kim, 2001). Similarly, the area in left inferior precentral gyrus (BA 6), extending into the inferior frontal gyrus (BA 9) has been proposed to be involved in ariculatory processes (Pulvermüller, et al, 2006) and sub-vocalization activity (Dietz, et al, 2005), as well as in certain naming and word-retrieval tasks (Etard, et al, 2000;Grabowski, et al, 1998). Therefore, like the left insula, these regions may be involved in lexical retrieval or covert naming of the F and U objects.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, in past studies, the inferior frontal gyrus has been repeatedly found to be activated during phonological processing, in phoneme monitoring, syllable counting and rhyming tasks (e.g., Démonet et al, 1992Démonet et al, , 1994Paulesu et al, 1993;see Poldrack et al, 1999;Démonet, Thierry and Cardébat, 2005;Vigneau et al, 2006, for a review), as well as during auditory speech perception (e.g., Wilson et al, 2004;Watkins and Paus, 2004;Pulvermuller et al, 2006;Wilson and Iacoboni, 2006). This region thus appears well adapted to syllable parsing process in the present verbal transformation task (Sato et al, 2004), and to speech segmentation in general (Burton and Small, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-known fact that speech production is tightly related to the motor cortex, some studies have shown that the motor cortex is activated in speech perception tasks [24][25][26][27][28][29][30] . For example, when listeners [26,27] , suggesting that different speech stimuli activate motor cortical regions with different patterns.…”
Section: Anatomical and Functional Associations Between The Auditory mentioning
confidence: 99%
“…For example, when listeners [26,27] , suggesting that different speech stimuli activate motor cortical regions with different patterns. In other words, listening to various verbal stimuli may cause differential automatic activations of cortical regions involved in speech production.…”
Section: Anatomical and Functional Associations Between The Auditory mentioning
confidence: 99%